CHINA AND ENERGY SECURITY IN CENTRAL ASIA - GUANG, Pan (CENTRAL ASIA AND THE CAUCASUS, 2007)
This paper is divided into three parts: China’s energy policy and energy development strategy; Central Asia’s significance for China’s overseas energy development strategy; and Central Asia’s energy security and energy development.China has now surpassed Japan as the second largest energy consuming country, next only to the United States. In 2006, China imported 145.18 million tons of crude oil, making another record in history.1 It is expected that by 2010, China could import 180 to 200 million tons of crude oil, over half of its total consumption.2 Meanwhile, with the steady rise in energy consumption, environmental pollution as well as energy waste will increase, presenting a host of serious challenges to the govern-ment and society. In the face of such a situation, China has begun to gradually adjust its energy policy and energy development strategy, as reflected in the following five areas:Energy production in the western part of the country is being encouraged, while in the eastern part it is becoming stabilized. To ensure adequate domestic production, the old oil (including gas) fields in eastern China, some of which are already peaking out, are now giving way to the emerging fields in the west, with the latter becoming the new focus of energy development.eanwhile, energy output, such as the gas produced in the west, is being transported to the eastern part of the country as a corresponding measure. Energy development is thus becoming a key component of China’s national strategy for “developing the country’s west.”The energy consumption structure is being remodeled. In China’s energy mix, the proportion of coal is to decrease from its current level of 65%-69%, while that of oil, gas, hydro-power and nuclear power will increase from their current levels of 20%-25%, 3%, 6% and 1%, respectively. It is expected that by 2020, coal will account for 54%, with oil increasing to 27%, gas to 9.8%, and hydro and nuclear power to 9.1%. Of course, new sources of energy will be developed as well, just as clean coal technology will be promoted.